The Role of Principals’ Transformational Leadership in Conflict Management to Improve Teacher Performance: A Multisite Study at SDN Grati I and SDN Ranuklindungan II, Grati District - Ika Prasurya Fadliastuti; Taufiq Harris; M. Furqon Wahyudi (The Future of Education Journal, 2025)
This study aims to analyze the role of principals’ transformational leadership in conflict management to improve teacher performance through a multicase study conducted at SDN Grati I and SDN Ranuklindungan II, Grati District, Pasuruan Regency. This study is motivated by low teacher performance influenced by horizontal and vertical conflicts, high administrative workloads, and low work motivation. Conflicts that are not managed effectively tend to be dysfunctional; however, through transformational leadership characterized by the dimensions of idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration, conflicts can be managed constructively. This research employed a qualitative approach with a multisite case study design. Data were collected through participatory observation, in-depth interviews, and document analysis. The findings indicate that transformational leadership is effective in managing conflicts through collaboration and compromise strategies, thereby creating a conducive work climate, enhancing work motivation, promoting instructional innovation, and improving teacher performance. Supporting factors include a collaborative culture and policy support, while inhibiting factors consist of budget limitations and resistance to change. The resulting conflict management model is adaptive to the school context.